Bridges or traps? Casualisation and labour market transitions in Australia - Watson, I (My University, 2013)
In this article I re-examine the familiar debate on whether casual jobs represent a ‘bridge’ into permanent employment, or a ‘trap’ which keeps workers locked into ongoing casualised work or joblessness. My analysis looks at the labour market destinations of casual workers over time, making use of the HILDA data for the period 2001 to 2009. The novelty of my approach is two-fold. I examine an extensive range of individual, locality and job characteristics to assess which of these are most strongly associated with various labour market destinations. Secondly, I conduct the analysis using longitudinal panel data, in which I make use of random intercepts multinomial logit panel models to estimate various conditional predicted probabilities for these destinations. The findings show that as far as individual characteristics are concerned, age and years in paid employment matter a great deal, while education matters much less. Increasing age leads to worse outcomes, more years in paid employment lead to better outcomes, and increased levels of educational qualification have only a modest link to better outcomes. In regard to locality, the more disadvantaged the area, the more likely that casual jobs will persist, transitions to permanent jobs will diminish and transitions to joblessness increase. In regard to the jobs themselves, casualization persists in those industries where casual density is high, where organisations are small, where the work is part-time, and where skills development is limited. These findings suggest that systemic influences count for a great deal, while human capital elements count for much less. I conclude that the very nature of casual jobs is itself responsible for perpetuating casualised employment.
Keywords: Employment -- Hours; Education and Training; Employment -- Labour force participation; Learning, education and training; Labour market; Education and Training; Employment; Hours; Labour force participation; Learning, education and training; Employment and unemployment